Highly textured zinc aluminate: Nd, Ce films over sapphire for NIR emitting applications. Issue 8 (15th April 2023) - Rojas-Hernandez, Rocío Estefanía; Rubio-Marcos, Fernando; Serrano, Aida; Román-Sánchez, Sara; Fernandez, José Francisco; Hussainova, Irina
Abstract: The development of sapphire-compatible optical sources is highly valued due to the potential cost-effective applications in sapphire-based integrated devices. In this work, a screen printing technique assisted by a molten salt flux was used to synthesize ( hk0 )-textured ZnAl2 O4 : Nd, Ce sub-micron films deposited over the sapphire substrate. The study is focused at controlling Ce concentration in the emitting layers, as well as determining the key parameters to be met for the development of ZnAl2 O4 -based films of high efficiency and remarkable optical properties. A degree of crystallinity of the ZnAl2 O4 -based films, and a precise adjustment of texture are the keys parameters for further improvement of NIR luminescence efficiency. Specifically, ( hk0 )-textured films were developed at sintering temperature of around 1300 °C, which contributed to a higher NIR emission intensity as compared to that of ( hkl )-untextured films. Therefore, the design process carried out in this work promotes a feasible way to achieve a high NIR emission performance, demonstrating the validity of the approach for a wide range of applications. Graphical abstract: Modulating the texture of ZnAl2 O4 : Nd, Ce sub-micron films growth over sapphire substrates to enhance the NIR luminescence. Image 1